Penilaian Asset dalam Akuntansi Syari’ah - Muhammad Muhammad (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2003)
This article aims to discuss the conceptual development of the asset assessment on Syari’ah accounting. From the perspectives of postulates, assumptions and principles, the conventional and Syari’ah accounting are totally different, including in the area of the system and technique of asset valuation. The value assessment of asset in Syari’ah accounting relies on the size of the asset. The valuation techniques of asset such as discount factor, time value of money seems inaccurate measures of asset. The concept of current cash equivalent may fit for the asset valuation in Syar’iah accounting.Keyword: zakat, concervatism, discout factor, time value of money; current cash equivalent